THE EFFECT OF THE USING PICTURE AND PICTUREMODEL ON STUDENTS’ WRITING ABILITY IN PROCEDURE TEXT TO THE TENTH GRADE OF SMA NEGERI 1 ANGKOLA TIMUR - Samsul Siregar (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: This study aims to know whether there is a significant effect of the using picture and picture model on students’ writing ability in procedure text to the tenth grade of SMA Negeri 1 Angkola Timur. The research was conducted by using experimental method (pretest posttest one group design) with 69 students as the sample and they were taken by using cluster sampling technique from 102 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of the using picture and picture model was 2.90 (good category) and b) the average of students’ writing ability in procedure text before using picture and picture model was 69.49 (enough category) and after using picture and picture model was 77.01 (good category). Furthermore, based on inferential statistic by using ttest one tail, it could be found ttable was less than ttest (9.05 > 1.667). It means, there is a significant effect of the using of picture and picture model on the writing’ ability in procedure text to the tenth grade students of SMA Negeri 1 Angkola Timur. Keywords:Picture and picture model and writing procedure text Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui apakah ada pengaruh yang signifikan dari penggunaan model gambar dan gambar terhadapkemampuan menulis siswateks proceduredi kelas X SMA Negeri 1 Angkola Timur. Penelitian ini menggunakan metode eksperimen dengan desain penelitian pra-eksperimental; satu kelompok pre-test post-test design. Populasi dalam penelitian ini adalah semua siswa kelas sepuluh yang terdiri dari 102 siswa.Teknik sampling yang digunakan pada penelitian ini adalah cluster sampling dan jumlah sampel terdiri dari 69 siswa. Dalam mengumpulkan data, peneliti menggunakan lembar observasi untuk mendapatkan data dalam penggunaan model pembelajaran gambar dan gambar dan tes untuk mendapatkan data kemampuan siswa dalam menulis procedure text. Peneliti menggunakan proses statistik dalam menganalisis dengan menggunakan rumus uji t. Berdasarkan data yang telah dianalisis, hasil analisis data menunjukkan bahwa t hitung lebih tinggi dari ttabel >ttest (9.05 > ttabel 1,667). Jadi, hipotesis diterima. Ini berarti ada pengaruh signifikan penggunaan model pembelajaran gambar dan gambar terhadap terhadap kemampuan menulis siswateks proceduredi kelas X SMA Negeri 1 Angkola Timur. Kata kunci: model pembelajaran gambar dan gambar, procedure teks.